Mathematical genius Mihailo Petrović: Mika Alas (1868-1943) - Jandrić Miroslav (Scientific Technical Review, 2018)
It has been 150 years since the birth of a great Serbian mathematician, academician Mihailo Petrović - Mika Alas. He upgraded his inborn talent for natural sciences at the Belgrade's Grand School (Grande ėcole) where he graduated in mathematics in 1889. In France, at Sorbonne, as the best student of generation in 1892, he obtained a graduate degree in mathematical sciences, and subsequently a graduate degree in physics in 1893. He defended his doctoral dissertation in 1894 in front of the commission made of then most famous world mathematicians Emile Picard, Charles Hermite and Paul Painlevė. Upon acquiring the title of Doctor of Philosophy in Mathematical Sciences, he returned to Serbia and became a professor at the Belgrade's University. With a bunch of published scientific papers that referred to differential equations, numerical analysis, geometry of polynomials and mathematical phenomenology, Mihailo Petrović was the owner of numerous patents. Some of the most significant patents that have found the outstanding practical application around the world are: artillery depth measurer, device for launching the missiles, automatic automobile gear, eternal calendar, etc. The academician Petrović was not only a mathematician and scientist, yet he was a cryptographer, world traveler, travel writer, musician, ichtiologyst and above all a fisherman. His passion for fishing brought him a recognizable nickname Mika Alas - river fisherman.